Impact Of The Work Environment And Operating Strategy On Operational Performance In Embroidery Company Noor Anisa Collection Tasikmalaya City - Nurul Mardiana; Suci Putri Lestari; Barin Barlian (Penerbit Jurnal Indonesia, 2022)
This research aims to find out the Simultaneous and Partial Influence between the Work Environment and Operating Strategies on Operational Performance at The Noor Anisa Collection Embroidery Company in Tasikmalaya City. The research method used is a survey method with a quantitative approach. With the sample used is a saturated sample. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 24. The results showed simultaneously the work environment and operating strategies significantly affected operational performance. Partially the work environment has a significant effect on operational performance. Partially operating strategies significantly affect operational performance.